Perspectives of conservation from multiple actors: the case of Chicamole Ecological Preservation Zone, Mexico - Calva-Soto, Karina; Bravo-Cadena, Jessica; Ortega-Meza, Daniela; Pulido-Silva, María Teresa (BOSQUE, 2019)
In Mexico, State Natural Protected Areas are frequently undervalued and rarely studied. The objective of this work was to analyze the process of decree and governance features of Chicamole Ecological Preservation Zone, which protects a cloud forest. An actor map was generated to understand the organization scheme, the external sector involved and their relationships. Semi structured Interviews were conducted both with governmental institutions and local inhabitants to analyze the decree. In spite of the obtained differences in perception, it can be noted that major conservation resulted from legislation. In addition, the presence of well-defined community norms regarding the use of natural resources (especially firewood and water) has encouraged forest conservation. This study shows the importance of a small area in the context of the protected areas in Mexico. The challenges of Chicamole Ecological Preservation Zone include increasing the interaction between sectors, achieving local recognition of the protected zone, and strengthening the social organization and the sustainable use of natural resources through stakeholder inclusion.